Baicalein Triggers Mitochondria-Mediated Apoptosis and Enhances the Antileukemic Effect of Vincristine in Childhood Acute Lymphoblastic Leukemia CCRF-CEM Cells. (29th January 2013) - Chen, Yun-Ju; Wu, Chieh-Shan; Shieh, Jeng-Jer; Wu, Jyh-Horng; Chen, Hsing-Yu; Chung, Ting-Wen; Chen, Yu-Kuo; Lin, Chi-Chen
Abstract : Acute lymphoblastic leukemia (ALL) accounts for approximately 75% of childhood leukemia, and chemotherapy remains the mainstay therapy. Baicalein is an active flavonoid used in traditional Chinese medicine and has recently been found to have anticancer, anti-inflammatory, and antiallergic properties. This study aims to investigate the molecular apoptotic mechanisms of baicalein in CCRF-CEM leukemic cells and to evaluate the combined therapeutic efficacy of baicalein with several commonly used chemotherapeutic drugs in CCRF-CEM cells. Our results demonstrate that baicalein induces mitochondria-dependent cleavage of caspases-9 and -3 and PARP with concomitant decreases in IAP family proteins, survivin, and XIAP. Furthermore, our results present for the first time that baicalein triggers a convergence of the intrinsic and extrinsic apoptotic pathways via the death receptor-caspase 8-tBid signaling cascade in CCRF-CEM cells. In addition, we also present for the first time that the combination of baicalein and vincristine results in a synergistic therapeutic efficacy. Overall, this combination strategy is recommended for future clinical trials in the treatment of pediatric leukemia owing to baicalein's beneficial effects in alleviating the vomiting, nausea, and skin rashes caused by chemotherapy.